Can the ethnic differences in IVF cycle outcome be influenced by the impact of BMI?. (1st October 2020) - Mascarenhas, Mariano; Kulkarni, Mugdha; Balen, Adam
Abstract: The objective of this study was to investigate the role of Body Mass Index (BMI) in influencing ethnic variation in IVF outcomes. This retrospective cohort study included women (having BMI between 19 to 30 kg/m 2 ) undergoing their first IVF cycle with fresh blastocyst transfer at a single IVF unit between 2010 and 2015. In summary, South Asian women had a lower live birth rate (LBR) (27% vs 44.7%, aOR 0.41, 95% CI 0.29 to 0.59) than Caucasian women. Subgroup analysis revealed a significantly lower LBR for South Asian women when their BMI was 25–25.9 kg/m 2 (21.4% vs 47.4%, aOR 0.19, 95% CI 0.04 to 0.84), 26–26.9 kg/m 2 (30.0% vs 55.0%, aOR 0.26, 95% CI 0.08 to 0.86) and 27–27.9 kg/m2 (14.3% vs 39.4%, aOR 0.14, 95% CI 0.03 to 0.70) with no significant differences in the other BMI subgroups. These results suggest that a lower BMI cut-off may be indicated for South Asian women having IVF when compared to Caucasian women. These findings are novel but are limited because they are from a single centre. However, the results should prompt further research into the subject by multi-centre studies with larger number of IVF cycles analysed.